The Management of Character Education in Schools Around Pesantren Environment to Build Akhlakul Karimah - Deti Rostini; Atabik Zuhdi; Vidia Lantari Ayundhari (DINASTI RESEARCH, 2020)
Character education in Islam has existed since Prophet Muhammad’s period. “Pesantren” or Islamic boarding school is a place of character building in obedience to “Kaffah” Islamic teachings. The character education in schools here means, a process of building good character or Akhlakul Karimah by presenting education model of pesantren but realized in formal institutions. It is deemed as solution for children who do hesitate to have boarding school education because of several reasons. This study aims to describe the implementation of character education management in senior high schools around boarding schools environment located in Banyumas, Central Java. The approach used in this research is a qualitative with descriptive method. The character education in Banyumas has implemented four modern management functions in a proportional way by upholding the tutor role of Pesantren.. The cooperation has been running simultaneously and run conventionally, while still adhering the management principles even need a various ongoing renewal efforts.